We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+5
529
2
avatar+305 

solve          −(2x+1)+4x=13+2(1+5x)

 Jan 28, 2017

Best Answer 

 #1
avatar+102761 
+10

−(2x+1)+4x=13+2(1+5x)

 

\(\begin{align} −(2x+1)+4x&=13+2(1+5x)\\ [−1(2x+1)]+4x&=13+[+2(1+5x)]\\ [-2x-1]+4x&=13+[2+10x]\\ -2x-1+4&=13+2+10x\\ -1+2x&=15+10x\\ -1+2x\textcolor{blue}{-2x}&=15+10x\textcolor{blue}{-2x}\\ -1&=15+8x\\ -1\textcolor{blue}{-15}&=15+8x\textcolor{blue}{-15}\\ -16&=8x\\ -2&=x\\ x&=-2\\ \end{align} \)

.
 Jan 28, 2017
 #1
avatar+102761 
+10
Best Answer

−(2x+1)+4x=13+2(1+5x)

 

\(\begin{align} −(2x+1)+4x&=13+2(1+5x)\\ [−1(2x+1)]+4x&=13+[+2(1+5x)]\\ [-2x-1]+4x&=13+[2+10x]\\ -2x-1+4&=13+2+10x\\ -1+2x&=15+10x\\ -1+2x\textcolor{blue}{-2x}&=15+10x\textcolor{blue}{-2x}\\ -1&=15+8x\\ -1\textcolor{blue}{-15}&=15+8x\textcolor{blue}{-15}\\ -16&=8x\\ -2&=x\\ x&=-2\\ \end{align} \)

Melody Jan 28, 2017
 #2
avatar+8457 
+5

solve −(2x+1)+4x=13+2(1+5x)

 

\(-(2x+1)+4x=13+2(1+5x)\)            to calculate

 

\(-2x-1+4x=13+2+10x\)           

                                         Change of page with change of sign

 

\(-8x=16\)                                                            divide by -8

 

\(x=-2\)

 

laugh  !

 Jan 28, 2017

9 Online Users

avatar
avatar